Komodifikasi Pekerja dan Dampaknya pada Kualitas Pemberitaan di YouTube KompasTV - Sadryna Evanalia; Abdul Rochim; Siti Fatimah (Universitas Prof. Dr. Moestopo (Beragama), 2023)
In the digital era, some media use YouTube to distribute their content to get new profit opportunities from social media. This study aims to determine the commodification of workers on YouTube KompasTV and determine its impact on the quality of the news. The research uses qualitative methods with a case study approach and data collection is carried out through observation and interviews. The results of this study found that the heavy work done by media workers and the low wages of media workers meant that the practice of commodification continued. Youtube KompasTV is one of the media's efforts to maintain its existence so that the creativity of creator content is proof of the commodification of workers which provides benefits for the media. Regarding the quality of news coverage, this study found that content creators generally only pursue what is the habit of public consumption, so the news that is broadcast is generally only carried out to meet normative quality standards. This study found that KompasTV content creators experience a process of exploitation, alienation, mystification, reification, and normalization.